Problems of system of training for the tourist industry in Russia - E. R. Orlova; E. N. Koshkina; M. V. Koshkin (Путеводитель предпринимателя)
Now tourist activities are positioned as one of priority industries of economy of Russia, but full development of the Russian tourism requires significantly bigger number of professional specialists. In the article the analysis of distribution of the profile educational organizations in the territory of Russia is carried out, the directions on enhancement of system of training, increase in professionalism of workers in a tourist industry are offered.